Prediction rain attenuation effect on free space optical communication Kuching/Samarahan Region - Abdul Rahman, Kram; S. A., Kwang Thai; Rosdisham, Endut; S. A., Aljunid; N., Ali; Che Beson, M. Rashidi (American Institute of Physics, 2024)
Rain attenuation is significantly affecting the FSO performance of a free-space optical communication system. Kuching/Samarahan region is situated in Malaysia state which is under tropical climate zone. The rain distribution is recorded high due to having rain season year-round. It worst when turn to monsoon season where the precipitation rate is expected high and dense. It is crucial to design the effect FSO system to ensure good quality transmission beam signal. This paper is focus on Kuching/Samarahan zone as the preliminary result to investigate the rain pattern and effect over FSO propagation. The investigation it focuses on that region is due to development that area to implement fully digital economy which need supported by high speed and capacity data that can be produced by optical technology. Therefore, FSO technology can perform this task. The rain data is collected from Malaysia Meteorology Department (Met Malaysia) which for three years 2017, 1018 and 2019. The performance will measure the effect of scattering coefficient, rain attenuation and geometrical loss. It is expected heavy rain will contribute the great impact over FSO link.